Investigation of the impact of food and insecurity to the nutritional status of children 6 to 71 months using the Radimer Cornell Questionnaire among the rural poor in Brgy. Nabitasan, Leganes, Iloilo - Chan, Tsarina Matta; Erum, Lesley Lopez; Galas, Caryl Estranero; Hernandez, Yryka Elevado
One of the main objectives of the United Nations? Sustainable Developmental Goals (SDGs) is to achieve zero hunger through food security. Within the Municipality of Leganes, Barangay Nabitasan has consistently ranked as the barangay with the most cases of undernourished children aged 6-71 months old. Nabitasan is located 5 kilometers away from poblacion and the locals are handicapped by their limited purchasing power and source of water and their lack of alternative source of food. Accordingly, this cross-sectional study investigated the impact of food insecurity to the nutritional status of 159 children aged 6 to 71 months old in Barangay Nabitasan, Leganes, Iloilo. The children?s nutritional status was determined based on their Weight for Age (WFA) while the respondents for the Radimer/Cornell Questionnaire were the respective mothers or guardians of the children. The Radimer/Cornell Hunger Scale was utilized to measure food security in terms of hunger. Additionally, the results of the scale were correlated to the following sociodemographic factors: age of the mother/guardian, annual family income, income allotment for food, household size, number of children, sibling rank, food source, educational attainment of the mother/guardian. Using chi square test it was found that there was a significant relationship between food security and the nutritional status of the children (X2=5.729, df=1, p-value<0.05). Odds ratio showed that a child that belongs to a food secure household is 2.715 times more likely to be normal than a child that belongs to a food insecure household. Furthermore, factors that were associated with food security were identified through logistic regression. 8 covariates were included in the analysis and the generated model identified the covariates that contributed most and were significantly associated with food security. The model tells us that: 1.) Increasing annual family income was associated with an increased likelihood of being food secure 2.) increasing number of children was associated with a decreasing likelihood of being food secure and 3.) having both market and alternative food source, compared to those who rely on market alone, increases the likelihood of being food secure. It is significant to note that the model generated by this study correctly predicted 76.1% of the observed food security status of the cases; this may indicate that there are still other important determinants of food security that have not been identified and that further studies should consider including these.